Effect of Pinus taeda Hydrolyzed Lignin on Biochemical Profile, Oxidative Status, and Semen Quality of Healthy Dogs - Aiudi, Giulio G.; Cicirelli, Vincenzo; Maggiolino, Aristide; Burgio, Matteo; Bragaglio, Andrea; Tateo, Alessandra; De Palo, Pasquale (Frontiers in Veterinary Science, 2022)
Sub-fertility represents a frequent challenge in canine reproduction. Use of micronutrients and/or additives was investigated as approach to improve sperm quality, which are the main constraints on reproduction in canine species. Although some information is available about the effect of a daily supplementation with substances presenting antioxidant/antioxidative activity on semen quality, the aim of this paper is to observe the effect of a polyphenolic mix of substances derived from hydroxylation of Pinus Taeda lignin (PTHL). For the trial, 40 male dogs were involved, 20 received PTHL for 90 days and 20 were left untreated serving as control group. Every 30 days blood and semen samples were collected and analyzed. The biochemical profile of both groups was not affected by treatment and time (P > 0.05). Differently, dogs that received PTHL showed higher blood superoxide dismutase, catalase and glutathione peroxidase activity (P < 0.01). Moreover, the dietary addition of PTHL can significantly increase the semen volume, concentration and spermatozoa motility (P < 0.01) in healthy dogs. The PTHL supplementation represents a good way to enhance dogs’ semen quality and improves the antioxidant status of animals.